COMPARISON OF PROLONGATION OF ANALGESIA AND CONSUMPTION OF OPIOIDS IN PATIENTS GIVEN SAB WITH LOCAL ANESTHESIA ALONE VERSUS WITH TRAMADOL AS ADJUVANT THERAPY UNDERGOING LOWER LIMB SURGERY - SHEIKH, NG; JAVED, HM; SHEIKH, MG; AVAIS, B; BUTT, Z; JAMSHAID, B (Biological and Clinical Sciences Research Journal, 2023)
The purpose of this study was to determine whether or not adding intrathecal tramadol to bupivacaine for lower limb procedures increased the duration of analgesia and decreased the mean post-operative opioid intake. This research was carried out between June 1 and November 30, 2022, in the Department of Anaesthesiology at Aziz Bhatti Shaheed Teaching Hospital in Gujrat, Pakistan. Non-probabilistic sequential sampling was used to pick the patients. One hundred patients from the ASA I, II, and III categories who met the inclusion criteria and were scheduled for lower limb surgery were randomly assigned to one of two groups. The tramadol-bupivacaine group (T) was given 15 milligrams of tramadol and 10 milligrams of bupivacaine (0.5 percent). In comparison, the bupivacaine-alone group (B) was given 1 milliliter of saline and 10 milligrams of bupivacaine (0.5 percent). The duration of analgesia was recorded by tracking the time until the patient first asked for pain medication. The average amount of opioid analgesia taken by both groups in the first 24 hours after surgery was also compared. SPSS version 22 was used for the data analysis. Anesthesia lasted much longer, 174.26 ± 15.21 minutes in the tramadol group, compared to 132.5 ± 14.48 minutes in the bupivacaine group. (p = 0.006). As expected, there was a significant (p 0.001) reduction in 24-hour opioid intake (308.2 ± 23.8) in group T compared to group B (470.5 ± 36.2mg). This research confirmed that intrathecal tramadol (15mg) could be safely used with bupivacaine in subarachnoid blocking to increase the duration of analgesia and reduce the need for opioids in the post-operative period following lower limb procedures.